Much to see and do up north - Teh, Alan Leam Seng (New Straits Times, 2012)
HONESTLY, I had some reservations abaut this trip to Universiti Utara Malaysia as I thought there's nothing much except for libraries, lecture halls and dormitories filled with bespectacled students going around with their heads buried in books thicker that the telephone directory in my hall.